Enhancing Critical Thinking Skills through Islamic History Learning: Study at UIN Raden Intan Lampung - Uswatun Hasanah; Khoirul Umam Addzaky (Bustanul Ulum Journal of Islamic Education, 2025)
Learning Islamic History in Islamic Higher Education poses a challenge in developing students' critical thinking skills. This is essential for a deeper understanding of Islamic values and the significance of history in Islamic History. While numerous studies have been conducted on the subject, there is no comprehensive study that examines the design and enhancement of students' critical thinking skills in learning Islamic History, specifically in Islamic higher education institutions in Lampung province. This study aims to investigate the challenges faced and find successful strategies to promote critical thinking based on empirical data from UIN Raden Intan Lampung. Using a qualitative approach with field research, this study involved 4 Islamic History lecturers and 12 students from the Islamic Religious Education Study Program, class of 2022. Data was collected through interviews, observation, and documentation, and then validated through triangulation. The results revealed key challenges include the dominance of cognitive-centered instruction with limited attention to affective and psychomotor development, limited time, low student interest, and monotonous methods. Successful strategies identified included the use of student-centered learning approaches with focus group discussions, contextual teaching and learning, problem-based learning, and appropriate utilization of technology. The implications of this study provide valuable guidance for educators and researchers to enhance Islamic history learning by strengthening critical thinking elements. This will ultimately improve the quality of Islamic history education at UIN Raden Intan Lampung, as well as other Islamic Higher Education institutions